(untitled) (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2025)
In the digital era, a basic understanding of technology and programming is crucial. However, many high school students view coding as something complicated and unattainable. This Community Service activity (PKM) aims to introduce the basic concepts of coding and programming logic in a fun and relevant way for students at MA Diponegoro Yogyakarta. The training titled "Coding is Fun! Developing Useful Applications" was held on September 4, 2025. The method used is an interactive approach that includes presentations, case studies on popular applications (such as Gojek, Shopee, and Instagram), an introduction to flowcharts to train systematic thinking, and group brainstorming sessions for application ideas. The results of the activity showed enthusiasm and active participation from the students. They were able to identify problems in their surroundings and design solutions in the form of simple application ideas in various fields. such as education, health, and social. This activity successfully fostered initial interest and provided a basic understanding that coding is a tool to create solutions that benefit society.